Barriers to home prepared meals in families with adolescents in urban underserved settlements of Jaffna municipality area - Menaka, S.; Arasaratnam, V.; Surenthirakumaran, R. (South Eastern University of Sri Lanka, 2025)
Sociodemographic barriers limit access to healthy food in underserved communities. This study explored barriers to home-prepared meals among adolescents aged 17–19 years in underserved settlements of the Jaffna Municipality area. Household visits were conducted in 100 homes, including observations of house structures, cooking facilities, and interviews using an interviewer-administered questionnaire. The sample comprised 48% males and 52% females, with families averaging 2.64 (±1.2) children and 1.68 (±0.6) adolescents. Severe overcrowding was identified, with 74% of households sharing a single residence and an average family size of 5.16 (±1.4). A major barrier was inadequate kitchen facilities; 36% lacked chimneys, reducing ventilation and cooking efficiency, while many relied on temporary kitchen setups. Moreover, 76% of households were nuclear families struggling with cooking in crowded conditions. Affordable nearby shops offering rotti and curry led 44% of households to purchase meals daily. These challenges highlight the need for interventions to improve infrastructure and promote healthier eating.
Keywords: Adolescents; Jaffna; Underserved settlements; Home prepared meals